2015
DOI: 10.1016/j.enbuild.2015.06.067
|View full text |Cite
|
Sign up to set email alerts
|

Luminous and solar characterization of PV modules for building integration

Abstract: Keywords:Building integrated photovoltaics BIPV Optical characterization PV module PV laminate PV glazing Spectrophotometry TransparencyThe optical characterization of different PV modules for integration in buildings (BIPV) is presented in this paper. The investigated PV modules are laminated glasses (PV laminates) suitable for integration in facades and windows. They are made of different PV cell technologies and some of them present a certain transparency degree, making possible to combine daylighting prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Furthermore, note the study of screening-engineered field-effect solar cells by Regan et al [118]. Other relevant studies on BIPV may also be found in the scientific literature [119][120][121][122][123][124][125][126][127][128].…”
Section: Various Aspectsmentioning
confidence: 99%
“…Furthermore, note the study of screening-engineered field-effect solar cells by Regan et al [118]. Other relevant studies on BIPV may also be found in the scientific literature [119][120][121][122][123][124][125][126][127][128].…”
Section: Various Aspectsmentioning
confidence: 99%
“…Although conventional PV modules have been used in agrivoltaics, the POSCAS is designed to test the performance of semi-transparent agrivoltaic specific PV modules. There are two primary types of semi-transparent PV that have mostly been used for building integrated PV(BIPV): (i) thin-film based semi-transparent PV, where in general the thickness of the active layer is adjusted to impact the transparency of the module and (ii) modules using crystal silicon technology where the spacing between cells is adjusted to adjust transparency [113][114][115][116][117]. This latter method also includes crystalline-silicon spherical solar microcells [118].…”
Section: Agrivoltaic Module Experimental Design With a Poscasmentioning
confidence: 99%
“…To obtain the luminous and solar characteristics, the transmittance and reflectance spectra have been determined (measurement error ± 1%) in the wavelength range of 250 to 2500 nm (see Figure 1), with a Perkin Elmer ® Lambda 900 UV/vis/NIR spectrophotometer equipped with an integrating sphere. The optical characterization of the PV modules and of the electrochromic smart windows follows the methodology suggested by [13] for semi-transparent PV modules, based on the standard EN 410 [28], which is also the document considered in EN 50583. The standard, which is equivalent to the international ISO 9050, specifies the methodology for determining the luminous and solar characteristics of glazing in buildings, allowing the comparison of different types of elements.…”
Section: Approachmentioning
confidence: 99%
“…For that purpose, it is firstly necessary to characterize the optical and thermal properties of these elements, and to analyze how these properties change as a function of their design parameters, such as transparency or glazing structure. Several works can be found in the literature on the energy assessment of buildings with STPV façades [11][12][13][14][15] or ECSW dynamic glazing [16][17][18]. These studies report the best energy saving potential in each location and building type, after analyzing the influence of parameters such as the PV module transparency, the window-to-wall ratio, or the type of glass structure, ranging from single glass to multiple glazing insulated windows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation